Trade in Health Services in the ASEAN Region - Arunanondchai, Jutamas; Fink, Carsten (World Bank, Washington, DC, 2012)
Promoting quality health services to large population segments is a key ingredient to human and economic development. At its core, healthcare policymaking involves complex tradeoffs between promoting equitable and affordable access to a basic set of health services, creating incentives for efficiencies in the healthcare system, and managing constraints in government budgets. International trade in health services influences these tradeoffs. It presents opportunities for cost savings and access to better quality care, but it also raises challenges in promoting equitable and affordable access. Drawing on a research project of the ASEAN Economic Forum, this paper offers a discussion of trade policy in health services for the ASEAN region. It reviews the state of healthcare in the region, existing patterns of trade, and remaining barriers to trade. The paper also identifies policy measures that could further harness the benefits from trade in health services and address potential pitfalls that deeper integration may bring about.